Demystifying the Citizen Soldier - Cohen, Raphael S. (RAND Corporation, 2015)
This report analyzes the National Guard's centrality to American national security, the idea that it prevents the United States from fighting controversial foreign wars, and its claim to embody the citizen soldier. It concludes that there are increasing tensions among these three ideals and that as the Guard has become an increasingly important tool of American national security, it has lost some of the attributes of the citizen soldier.